Peran Regulasi dalam Mewujudkan Perlindungan Konsumen yang Efektif - Pratista, Bunga Nuraini (Neolectura, 2025)
Consumer protection is one of the important aspects in creating a fair and sustainable market. In Indonesia, regulations related to consumer protection are regulated through Law Number 8 of 1999 concerning Consumer Protection, which aims to ensure that consumer rights are protected from detrimental business practices. However, even though this regulation already exists, its effectiveness still faces various challenges, such as weak supervision, lack of legal awareness among consumers, and rapid technological developments, especially in the e-commerce sector. The formulation of the problem is 1) How effective is the existing regulation in protecting consumer rights in Indonesia? 2) What is the role of supervisory institutions and law enforcement officers in implementing existing consumer protection regulations? The approach method used in this legal research is to use the normative legal approach method. The overall results of the research are that consumer protection regulations in Indonesia, especially those stated in Law Number 8 of 1999, have provided a good legal basis for protecting consumer rights. However, its effectiveness is still limited by various challenges, such as weak supervision, lack of understanding from consumers, and the rapid dynamics of the digital market and supervisory institutions and law enforcement officers have a very vital role in implementing consumer protection regulations in Indonesia. They are responsible for ensuring that consumer rights are effectively protected through supervision, law enforcement, and dispute resolution